Probiotics for the Control of Parasites: An Overview. (28th September 2011) - Travers, Marie-Agnès; Florent, Isabelle; Kohl, Linda; Grellier, Philippe
Abstract : Probiotics are defined as live organisms, which confer benefits to the host. Their efficiency was demonstrated for the treatment of gastrointestinal disorders, respiratory infections, and allergic symptoms, but their use is mostly limited to bacterial and viral diseases. During the last decade, probiotics as means for the control of parasite infections were reported covering mainly intestinal diseases but also some nongut infections, that are all of human and veterinary importance. In most cases, evidence for a beneficial effect was obtained by studies using animal models. In a few cases, cellular interactions between probiotics and pathogens or relevant host cells were also investigated using in vitro culture systems. However, molecular mechanisms mediating the beneficial effects are as yet poorly understood. These studies indicate that probiotics might indeed provide a strain-specific protection against parasites, probably through multiple mechanisms. But more unravelling studies are needed to justify probiotic utilisation in therapeutics.